Metallomic study of mercury in fish from Amazon region - Brazil - Moraes, Paula Martin de [UNESP]; Santos, Felipe André dos [UNESP]; Padilha, Cilene de Camo Federici [UNESP]; Castro, Gustavo Rocha de [UNESP]; Zara, Luiz Fabrício; Padlha, Pedro de Magalhães [UNESP] (E D P Sciences, 2013)
This paper presents preliminary findings for a metallomics study of mercury in the muscle of the fish from Amazonas region - Brazil, after protein separation by two-dimensional polyacrylamide gel electrophoresis (2D-PAGE) and subsequent evaluation of mercury by Thermal Decomposition and Amalgamation Coupled with Atomic Absorption (TTA-CAAS). It was found that mercury is present in 18 protein spots of dourada muscle (Brachyplatystoma rousseauxii) and 9 protein spots of pacu muscle (Myleus sp.). The protein spots in which they were determined the presence of mercury present molecular weight of 13.5 and 21.4 kDa and isoelectric point of 3.8 and 9.2, respectively.
Keywords: Mercury in fish; Metallomic study; 2D-PAGE; TTA-CAAS